Neurodiverse Online Conferencing - Urbistondo Cano, Francisco; Thibert, Dawn; Simon, Gail; Evans, Mairi; McEwen, Freda; Gordon-Jackson, Deni; Steare, David (Murmurations: Journal of Transformative Systemic Practice, 2022)
You can experience this Interactive Poster that we presented at the 2022 European Congress of Qualitative Inquiry. In this digital poster using the platform, MIRO, we share learning from designing and hosting the first online edition of the 3rd Autism and Systemic Practice and Research Conference. We describe how we used the online possibilities of Zoom to challenge some of the professional discourses on autism to create a more reflexive conference culture. We propose that good practice for neurodiverse attuned online conferences can be generalisable as good conference practice. Watch this 30 second introduction to the board first: https://www.youtube.com/watch?v=8ZI3m3OuVeg Then view the board: https://bit.ly/38UzNQw